2016
DOI: 10.1016/j.smallrumres.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of goat milk from Lebanese Baladi breed and his suitability for setting up a ripened cheese using a selected starter culture

Abstract: Characterization of goat milk from Lebanese Baladi breed and his suitability for setting up a ripened cheese using a selected starter culture.Small Ruminant Research http://dx.(N.P., Mangia) 2 Highlights The first manufacturing of ripened cheese from Baladi goat milk was proposed. Physicochemical and microbiological parameters were evaluated.  Thermophilic cocci were dominant during all cheese ripening.  Higher content of free fatty acids was observed. ABSTRACTIn this work the hygiene and quality parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…The conducted study showed a complete absence of the two dangerous pathogens Salmonella and sulphitereducing Clostridium in all examined samples of ewe's and goat's milk, suggesting that both pathogens are uncommon in small ruminant milk in the herds sampled. Tabet et al (2016) advanced a similar finding for goat's milk and by Fatima et al (2013) for sheep's milk. Various studies have shown that milk quality in small ruminants can be affected by several factors, including animal breed, milking practice, stage of lactation, farm characteristics and practices (Tonamo et al 2020), season (Kondyli et al 2012), animal health, housing conditions and feeding practices, flock size, and hygiene of premises and milk tank parlors (Carloni et al 2016).…”
Section: Microbiological Featuressupporting
confidence: 70%
See 1 more Smart Citation
“…The conducted study showed a complete absence of the two dangerous pathogens Salmonella and sulphitereducing Clostridium in all examined samples of ewe's and goat's milk, suggesting that both pathogens are uncommon in small ruminant milk in the herds sampled. Tabet et al (2016) advanced a similar finding for goat's milk and by Fatima et al (2013) for sheep's milk. Various studies have shown that milk quality in small ruminants can be affected by several factors, including animal breed, milking practice, stage of lactation, farm characteristics and practices (Tonamo et al 2020), season (Kondyli et al 2012), animal health, housing conditions and feeding practices, flock size, and hygiene of premises and milk tank parlors (Carloni et al 2016).…”
Section: Microbiological Featuressupporting
confidence: 70%
“…Higher TMAB, TCC, LAB, Y/M, S. aureus, and E. coli counts in ewe's milk were obtained by Fatima et al (2013). While in goat's milk, Tabet et al (2016) detected higher counts and Kalhotka et al (2015) reported higher bacterial results in both species. Lower total bacterial counts have been advanced in goat (Abd El Aal and Awad 2008) and sheep's milk (Tonamo et al 2020).…”
Section: Microbiological Featuresmentioning
confidence: 81%
“…The lowest FFA level, was 0.19±0.02%, found in unripen cheese and the level started to increase with the duration of 10 d ripening. The duration of ripening of 20 and 30 d had equal 0.52% to 0.57% FFA which started to increase after 10 d. The increased FFA during ripening was also reported in Baladi goat cheese (Tabet et al, 2016). …”
Section: Free Fatty Acid (Ffa)supporting
confidence: 65%
“…lactis LPS31 strains, Lactobacillus casei subsp. casei 3PS103 , and Streptococcus thermophilus SPS1 ( 47 ), etc., are different starter cultures usually utilized for semi-hard and hard cheese. In addition to starting culture, single strength rennet in milk and then allowing it to coagulate.…”
Section: Processing Of Goat Milk and Its Productsmentioning
confidence: 99%